Semantic Web Collaborative Spaces Second International Workshop, SWCS 2013, Montpellier, France, May 27, 2013, Third International Workshop, SWCS 2014, Trentino, Italy, October 19, 2014, Revised Selected and Invited Papers - Molli, Pascal; Breslin, John G.; Vidal, Maria-Esther (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2016)
This book constitutes the thoroughly refereed post-workshop proceedings of the Second International Workshop on Semantic Web Collaborative Spaces, SWCS 2013, held in Montpellier, France, in May 2013, and the Third International Workshop on Semantic Web Collaborative Spaces, SWCS 2014, held in Trentino, Italy, in October 2014. The 6 revised extended papers presented were carefully reviewed and selected from 10 submissions. The papers are grouped in topical sections on challenges in collaborative spaces, modeling collaborative communities and the role of semantics, semantic MediaWiki communities, and exploiting semantics in collaborative spaces.